Enrichment of Cancer‐Associated Fibroblasts, Macrophages, and Up‐Regulated TNF‐α Signaling in the Tumor Microenvironment of CMS4 Colorectal Peritoneal Metastasis - Eirik Høye; Chakravarthi Kanduri; Annette Torgunrud; Susanne Lorenz; Bjørn Edwin; Stein G. Larsen; Åsmund A. Fretland; Vegar J. Dagenborg; Kjersti Flatmark; Christin Lund‐Andersen (Cancer Medicine)
ABSTRACT Background Metastatic colorectal cancer (mCRC) is the main cause of CRC mortality, with limited treatment options. Although immunotherapy has benefited some cancer patients, mCRC typically lacks the molecular features that respond to this treatment. However, recent studies indicate that the immune microenvironment of mCRC may be modified to enhance the effect of immune checkpoint inhibitors. This study aimed to explore the metastatic tumor microenvironment (TME) by comparing cell populations in colorectal liver (CLM), lung (mLu), and peritoneal (PM) metastases. Methods RNA isolated from 20 CLM, 15 mLu, and 35 PM samples was subjected to mRNA sequencing and explored through TME deconvolution tools, consensus molecular subtyping (CMS), and differential gene expression and gene set enrichment analysis, with respect to the metastatic sites. Clinical data and KRAS/BRAF hotspot mutation status were also obtained for all the cases. Results The cell type fractions in the TME were relatively similar between the metastatic sites, except for cancer‐associated fibroblasts (CAFs), B cells, endothelial cells, and CD4+ T cells. Notably, PM showed enrichment for CAFs and endothelial cells, consistent with distinct pathways associated with metastatic growth and progression in the peritoneal cavity. PM with the mesenchymal subtype, CMS4, had increased CAFs, endothelial cells, and macrophages, along with up‐regulated genes related to TNF‐α signaling via NF‐κB, EMT, and angiogenesis. Conclusions Tumor samples from different metastatic sites exhibited a broadly similar TME in terms of immune cell composition, with some intriguing differences. Targeting CAF‐associated pathways, macrophages, and TNF‐α signaling through NR4A could represent potential novel therapeutic approaches in CMS4 PM.